Patients' memories from intensive care unit: A qualitative systematic review - Charlotte C. Maartmann‐Moe; Marianne Trygg Solberg; Marie Hamilton Larsen; Simen A. Steindal (Wiley, 2021)
Abstract Aim To identify and synthesize the evidence regarding adult patients' memories from their stay in the intensive care unit. Design A qualitative systematic review and meta‐synthesis. PROSPERO # CRD42020164928. The review employed the guideline of Bettany‐Saltikov and McSherry and the Enhancing transparency in reporting the synthesis of qualitative research guidelines. Methods Systematic search for qualitative studies published between January 2000 and December 2019 in Cumulative Index to Nursing and Allied Health, Medical Literature Analysis and Retrieval System Online, PsycINFO, and Excerpta Medica Database. Pairs of authors independently assessed eligibility, appraised methodological quality using Joanna Briggs's quality appraisal tool and extracted data. The analysis followed the principles of interpretative synthesis. Results Sixteen papers from 15 studies were included in the review. Three themes emerged: (a) memories of surreal dreams and delusions, (b) care memories from sanctuary to alienation and (c) memories of being vulnerable and close to death.